Q&A - Ask Doubts and Get Answers

Clear All

View All Answers (1)

G Gautam harsolia
We know that  cos 3x = 4 - 3cos x we use this in our problem we can write cos 6x as cos 3(2x)         cos 3(2x) = 4 - 3 cos 2x                          =    -                                                                                                                   =                                            = 32 - 4 - 48 + 24  -                           =   32  - 48 + 18 - 1  = R.H.S.

View All Answers (1)

G Gautam harsolia
We know that                    We use this in our problem   cos 4x = cos 2(2x)             =                =                                                      =  = R.H.S.

View All Answers (1)

G Gautam harsolia
We know that       and we can write tan 4x = tan 2(2x) So,       =                                                              =                                                      =                                                       =           = R.H.S.

View All Answers (1)

G Gautam harsolia
cot x cot2x - cot3x(cot2x - cotx) Now we can write cot3x = cot(2x + x) and we know that  So,                                 =   cotx cot2x - (cot2xcotx -1)            =  cotx cot2x - cot2xcotx +1             = 1  = R.H.S.
We know that  We use these identities                     =RHS
We know that   We use these  identities                                                                                                         R.H.S.
We know that We use these identities  R.H.S.
We know that We use these identities                                                                                                           R.H.S.
As we know that                                                                                                         R.H.S.
We know that            By using this , we get  sin5x + sin3x = 2sin4xcosx now nultiply and divide by sin x Now we know that By using this our equation becomes                                                       R.H.S.
We know that  We are using this identity  sin2x + 2sin4x + sin6x = (sin2x + sin6x) + 2sin4x  sin2x + sin6x = 2sin4xcos(-2x) =  2sin4xcos(2x)          ( cos(-x) = cos x) So, our equation becomes sin2x + 2sin4x + sin6x = 2sin4xcos(2x) + 2sin4x Now, take the 2sin4x common sin2x + 2sin4x + sin6x = 2sin4x(cos2x +1)           (   )                                      =2sin4x( +1 )      ...
As we know that    Now         By using these identities cos2x - cos6x = -2sin(4x)sin(-2x) = 2sin4xsin2x                  (  sin(-x) = -sin x                                                                                                     cos(-x) = cosx) cos2x + cos 6x = 2cos4xcos(-2x) = 2cos4xcos2x So our equation becomes                                                     ...
We know that  So,  Now,  we know that  By using these identities sin6x + sin4x = 2sin5xcosx sin6x - sin4x = 2cos5xsinx Now,  2sinAcosB = sin(A+B) + sin(A-B) 2cosAsinB = sin(A+B) - sin(A-B) by using these identities 2cos5xsin5x = sin10x - 0 2sinxcosx = sin2x + 0 hence                                                                           
We know that  [ cos(A+B) - cos (A-B) = -2sinAsinB ] By using this identity                                   R.H.S.
Multiply and divide by 2  Now by using identities -2sinAsinB = cos(A+B) - cos(A-B) 2cosAcosB =  cos(A+B) + cos(A-B)                                         R.H.S.
We know that  So, by using these our equation simplifies to R.H.S.
As we know that,    ,      ,                 and     By using these our equation simplify to                                                                                                R.H.S.
As we know that      and    So, by using these identities                                                                                                                           R.H.S
Multiply and divide by 2 both cos and sin functions We get, Now, we know that 2cosAcosB = cos(A+B) + cos(A-B)             -(i) -2sinAsinB = cos(A+B) - cos(A-B)               -(ii)  We use these two identities In our question A =                            B =    So,  As we know that By using this                                                                     ...
We know that,                                                    By using this we can write                                                        
Exams
Articles
Questions